Noun Phrases in ELF Authors’ Academic Writing - Timyam, Napasri (LEARN Journal: Language Education and Acquisition Research Network, 2024)
Studies of English academic writing have revealed a shift to a compressed style, with preferences for lexical and phrasal types of noun modifiers over clausal modifiers. However, condensed noun phrases may result in a loss of explicitness since they lack grammatical markers specifying the semantic relations between head nouns and modifiers. This study examines the types and characteristics of nominal modifiers in the academic prose of ELF, which has been found to be marked by explicitness and clarification to ensure efficiency of communication among non-native users. Data were from the introduction and method sections of 60 research manuscripts in language and linguistics submitted to a Scopus-indexed journal. The results show that ELF authors conform to the modern norm of academic prose, producing compressed noun phrases with lexical and phrasal modifiers, particularly adjectives, nouns, and prepositional phrases. However, these noun phrases are structurally explicit: many of them have only one or two modifiers, facilitating the comprehension process. Also, the most prevalent modifier is prepositional phrases, with prepositions explicitly signaling the semantic relationship between head nouns and modifiers. The results reflect the way experienced users shape ELF to achieve a balance between the contrasting goals of conciseness and explicitness, which are both vital in ELF academic prose.